Population Genetics of the Moon Crab Matuta victor (Fabricius 1781) on Java Island, Indonesia - Nur Ikhlas Syuhada; Achmad Farajallah; Ali Mashar (Tropical Life Sciences Research, 2026)
Genetic diversity is crucial in assessing biodiversity and is increasingly being utilised in conservation and management. This study aimed to analyse the population genetics of Matuta victor on Java Island. A total of 91 specimens was collected from 10 localities: Ujung Kulon, Pangandaran, Carita, Tanjung Pasir, Subang, Bancar, Banyuates, Ambunten, Situbondo and Banyuwangi. We obtained 801 bp fragments of COI mitochondrial DNA defining 38 different haplotypes, namely, 12 shared and 26 unique haplotypes. H1 was the most frequent, existing in eight localities. The haplotype diversity (Hd) and nucleotide diversity (π) ranged from 0.667 to 1 and 0.003 to 0.022, respectively. The overall haplotype diversity was high (Hd = 0.921), indicating the presence of many haplotypes across populations, while the overall nucleotide diversity was low (π = 0.018), suggesting only small genetic differences at the nucleotide level. AMOVA analysis showed a low level of genetic differentiation among the 10 locations (FST = 0.266). Neutrality tests indicated the potential population expansion of M. victor in several locations in Java. These findings are expected to constitute a significant first step in designing targeted and sustainable conservation strategies for this species in its diverse coastal habitats in Indonesia.